Metatranscriptomics Analysis Reveals Diverse Viral RNA in Cutaneous Papillomatous Lesions of Cattle. (March 2022) - Fernandes, Adriana O; Barros, Gerlane S; Batista, Marcus VA
Bovine papillomavirus (BPV) is associated with bovine papillomatosis, a disease that forms benign warts in epithelial tissues, as well as malignant lesions. Previous studies have detected a co-infection between BPV and other viruses, making it likely that these co-infections could influence disease progression. Therefore, this study aimed to identify and annotate viral genes in cutaneous papillomatous lesions of cattle. Sequences were obtained from the GEO database, and an RNA-seq computational pipeline was used to analyze 3 libraries from bovine papillomatous lesions. In total, 25 viral families were identified, including Poxviridae, Retroviridae, and Herpesviridae . All libraries shared similarities in the viruses and genes found. The viral genes shared similarities with BPV genes, especially for functions as virion entry pathway, malignant progression by apoptosis suppression and immune system control. Therefore, this study presents relevant data extending the current knowledge regarding the viral microbiome in BPV lesions and how other viruses could affect this disease.